PYROCHLORE CHEMISTRY FROM THE SOKLI PHOSCORITE-CARBONATITE COMPLEX, FINLAND: IMPLICATIONS FOR THE GENESIS OF PHOSCORITE AND CARBONATITE ASSOCIATION - Lee M.J.; Lee J.I.; Kim Y.; Garcia D.; Moutte J.; Williams C.T.; Wall F. (My University, 2006)
The phoscorite-carbonatite complex in the Sokli alkaline-carbonatite massif, northern Finland, comprises five stages of intrusions or phoscorites and carbonatites (P1-C1, P2-C2 and P3-C3 for phoscorites and calcite carbonatites; D4 and D5 for dolomite carbonatites). The phoscorites and calcite carbonatites at Sokli usually occur as pairs with the same mineral assemblages. Pyrochlore is found in the majority of rock types in the Sokli phoscorite-carbonatite complex, shows wide compositional variation and seems to preserve evolution trends of host rocks. Crystallization of pyrochlore begins from the P2-C2 phoscorite and calcite carbonatite and continues up to the latest D5 dolomite carbonatite. Pyrochlore in the early stage P2-C2 rocks has high U and Ta contents. These elements suddenly decrease from the P3-C3 rocks, on the other hand, Th and Ce contents increase. The compositions of the late generations from the D4 and D5 rocks are close to that of an ideal end-member pyrochlore with formula (Ca,Na)2Nb2O6F. The Nb/Ta ratio and F content of pyrochlore increase from P2-C2 to the latest D5 dolomite carbonatite. The composition and evolutionary history of pyrochlore from the phoscorites are distinguished from those of the associated calcite carbonatites. Pyrochlore from the calcite carbonatites shows larger A-cation deficiencies compared to those from the paired phoscorites. Ta and Zr contents are slightly higher in pyrochlore from the calcite carbonatites, whereas Ti is generally higher in pyrochlore from the associated phoscorites. Moreover, pyrochlore from the phoscorites always shows a longer and more complex crystallization history compared to that of the same stage carbonatites. This indicates that the chemical condition was clearly different in the two systems during the crystallization of pyrochlore. Based on these results, together with the previous mineralogical and geochemical studies on the Sokli phoscorite-carbonatite complex, we propose a liquid immiscibility process as the most possible segregation mechanism of the two associated rocks. The composition of pyrochlore in the late dolomite carbonatites is distinct and always lies on the evolutional trend of the earlier varieties. This implies that the dolomite carbonatites are the final magmatic products of the Sokli phoscorite-carbonatite system. Copyright © 2006 by The Geochemical Society of Japan.
Keywords: CARBONATITE; LIQUID IMMISCIBILITY; PHOSCORITE; PYROCHLORE; SOKLI